The economics of repeated extortion - Jay Pil Choi; Marcel Thum (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2003)
This paper provides a simple model of repeated extortion. In particular, we ask whether corrupt government officials' ex post opportunism to demand more once entrepreneurs have made sunk investments entails further distortion in resource allocations. We show that the inability of government officials to commit to future demands does not distort entry decisions any further if technology is not a choice variable for the entrepreneurs. The government official can properly discount the initial demand in order to induce the appropriate amount of entry. If, however, the choice of technology is left to the entrepreneurs, the dynamic path of demand schedules will induce entrepreneurs to pursue a fly-by-night strategy by adopting a technology with an inefficiently low sunk cost component. In this case, we show that the unique equilibrium is characterized by a mixed strategy of the government official in future demand. Our model thus explains why arbitrariness is such a central feature of extortion. We also investigate implications of the stability of the corrupt regime for dynamic extortion and discuss how our framework can be applied to other investment contexts involving the risk of expropriation.
Keywords: D9; H2; K4; L1; 330; corruption; repeated extortion; ex post opportunism; dynamic consistency; dynamic cream skimming; Korruption; Kriminalitätsökonomik; Konzession; Markteintritt; Sunk Costs; Spieltheorie; Theorie